Swiss Ball Training Interventions: Body Composition Modifications in Overweight Adults - Case, Randy D (Journal of Educational Research and Policies, 2025)
The objective of this study was to determine the impact of specific Swiss ball exercises on the body composition of overweight individuals. A sample of 30 overweight males aged 20 to 30 years was taken from the general population of the Gwalior area in Madhya Pradesh, India. The selected subjects were categorised into two groups: 15 participants in the Swiss ball abdominal exercise group (Experimental) and 15 in the Control group. The present study employed a purposive - random selection strategy to choose the sample. The Body Composition Analyser and the WHO's BMI standards table were utilised to measure body fat percentage. The BMI was readily computed using the subsequent formula. BMI = (Weight in kilogrammes / Height in meters squared). Following the evaluation of the pre - test for both groups, a Swiss ball workout program was implemented for a duration of 12 weeks as part of the experimental treatment. Following the conclusion of 12 weeks of Swiss ball abdominal exercise training, a post - test measuring body fat percentage was administered to determine the significant differences between the Swiss ball abdominal exercise group and the control group. The t - test was employed to evaluate the data. The Swiss ball abdominal workout group demonstrated a statistically significant improvement in body fat percentage in experimental group II compared to control group I at the 0.05 level of significance.